Microfluid mechanics : - Liou, William W. (McGraw-Hill, 2006)
The rapid progress in fabricating and utilizing microelectromechanical (MEMS) systems during the last decade is not matched by corresponding understanding of the unconventional fluid flow involved in the operation and manufacture of these small devices. Providing such understanding is crucial to designing, optimizing, fabricating and operating improved MEMS devices. Microfluid Mechanics: Principles and Modeling is a rigorous reference that begins with the fundamental principles governing microfluid